Ergonomics and Employee Satisfaction with Special Reference to Selected Branches of Rajshahi Krishi Unnayan Bank - Rahman, Mohammad Azizur; Hossain, Zahid; Azam Khan, Mohammad Rafiul (Technium Business and Management, 2022)
The study aims at examining the ergonomics practices in the banking sector of Bangladesh especially on Rajshahi Krishi Unnayan Bank (RAKUB) and strains to show the relationship between ergonomics and employee satisfaction in the workplace. This study conducted on the existing employees serving the said bank branches operating in Rangpur. The significance of ergonomics in the workstation was commenced in 1949 in the Ideas Bank in US. Ergonomics, a new design of applying sophisticated tools facilitates employees’ performance and general productivity ensuring congenial work environment. A theoretical framework has been developed showing the dependent variable and independent variables were showed. The study confirmed that there is highly significant relationship between ergonomics factors and employee satisfaction withe help of Pearson Correlation Matrix. Employee satisfaction is very much important for earning profit and maximizing wealth of the bank. The study explored specific factors such as working tools, health, body posture, acoustics, working time, working environment and distinctly analyzed these factors while data collection. Data were collected through Likert’s Five Point Scale and used SPSS software. For internal consistency and reliability test, used Cronbach’s Alpha (.958) and KMO (.625>.5) test for quantifying observations in this study. The study identified six considerable factors having the direct relation with employee satisfaction. The study explored some specific delinquent in the practices of ergonomics in the banks and suggested for overcoming the challenges as well.